Efficacy of cardiopulmonary resuscitation in the supine position with manual displacement of the uterus vs lateral tilt using a firm wedge: a manikin study. (8th May 2014) - Butcher, M.; Ip, J.; Bushby, D.; Yentis, S. M.
Summary: Prevention of aortocaval compression is essential for effective cardiopulmonary resuscitation in late pregnancy. This can be achieved by either lateral maternal tilt or lateral uterine displacement. Results from a previous manikin study show that a firm foam‐rubber wedge allowed successful chest compressions whilst providing stable and reliable lateral tilt. However, it did not investigate resuscitation in the supine position with manual uterine displacement. The aim of this study was to compare the effectiveness of chest compressions in a manikin in the supine position vs lateral tilt using a foam‐rubber wedge, both on the floor and on a typical patient bed. Overall, we found that compressions were easier to perform in the supine position (p = 0.007 (bed) and 0.048 (floor)), and with greater stability in the supine position on the floor (p = 0.011). The effectiveness of chest compressions was similar in both the supine/uterine displacement and the lateral tilt positions, suggesting that either method may be suitable for CPR.